THE EFFECT OF SELLING PRICE AND SALES VOLUME ON THE INCOME OF THE JAYA SHOP AT THE PGS WHOLESALE CENTER IN SURABAYA - Fahmi Ashari S Sihaloho; Zainal Fanani; Etty Widawati; Aisyah Darti Megasari (International Journal of Economics, Science, and Education, 2024)
This research aims to describe the effect of selling prices and sales volume on Toko Jaya income both partially and simultaneously. This type of research is quantitative research with associative-casual approach. The used of research population is accountancy report of Toko Jaya in 2018-2019 with the research sample in 24 months. Data collected by observation method, documentation method, internet research, and library research. The data analysis method used multiple linier regression analysis, F test, T test. The results showed that there was a positive and significant effect partially and simultaneously selling price on the Toko Jaya income. There was a positive and significant effect partially and simultaneously sales volume on the Toko Jaya income.